Crisis Management and Resolution for a European Banking System - Giustiniani, Alessandro; Bossu, Wouter; Fonteyne, Wim.; Gullo, Alessandro (Washington, D.C. : International Monetary Fund, 2010)
This paper proposes an integrated crisis management and resolution framework for the EU's single banking market. It comprises a European Resolution Authority (ERA), armed with the mandate and the tools to deal cost-effectively with failing systemic cross-border banks, and is designed to address many fundamental operational and incentive problems. It also seeks to reduce moral hazard and better protect countries against the risk of twin fiscal-financial crises by detaching banks from government budgets. The ERA would be most effective if it were twinned or combined with a European Deposit Insurance and Resolution Fund.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Fiscal Policy